Clinical manifestations and viral kinetics of people with Mpox: A case series during the 2023 outbreak in Taiwan - Kai-Hsiang Chen; Wang-Da Liu; Kuo-Chen Weng; Hui-Hou Chen; Shu-Yuan Ho; Yu-Shan Huang; Tzong-Yow Wu; Guei-Chi Li; Sui-Yuan Chang; Chien-Ching Hung (Journal of Microbiology, Immunology and Infection)
Monkeypox (Mpox) has emerged as a global threat since 2022. We reported 14 cases of Mpox in 10 people with HIV (PWH) and 4 people without HIV (PWoH), of whom 64.3% had sexually transmitted co-infections. Severe complications of Mpox and prolonged viral shedding might occur in both PWH and PWoH.